Hitler’s Voice: The Loudspeaker under National Socialism - Epping-Jäger, Cornelia (Intermédialités / Intermediality)

(untitled) (Revue intermédialités (Presses de l’Université de Montréal), 2011)
This article examines the mechanisms through which acoustic-political power was claimed in the era of National Socialism. It shows that the “loud speaker” as a technical medium, framed as an extensively communicative apparatus, was constitutive for National Socialism’s political culture. Different operative scenarios of the loudspeaker are analyzed with regard to new forms of spatial-acoustic development. As a result, the article brings to light the temporal re-structuring by which the technically and medially performed voices of National Socialist speakers, and Hitler in particular, were established.